2016
DOI: 10.1002/crat.201600087
|View full text |Cite
|
Sign up to set email alerts
|

Surfactant directed synthesis of mesoporous alumina and α‐alumina single crystal

Abstract: Mesoporous Al2O3 were positively synthesized via treatment of the freshly precipitated amorphous alumina gel using aluminium sulphate as aluminium source, and sodium dodecyl sulphate (SDS) as structure‐directing agent (SDAs). The microstructures, morphologies and textural properties of the as‐prepared materials were characterized by X‐ray diffraction (XRD), transmission electron microscopy (TEM) and thermo gravimetric analysis (TG‐DTA). The calcined product at 600 °C was highly porous in nature having a BET su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 17 publications
(14 reference statements)
0
9
0
Order By: Relevance
“…Similarly, through hydrothermal route, [40] successfully synthesized 3D flower-like ZnO architectures assembled with numerous nanosheets with the aid of SDS. It has also been demonstrated that SDS is a highly effective structuredirecting agent for producing box-like structures [41] and is observed elsewhere to cause complete suppression of the buckling phenomenon above an optimal value of 1% by weight [42]. Additionally, Blanch et al [39] found out that attractive depletion in SDS was preferential for carbon nanotubes of larger diameter at higher concentrations of SDS.…”
Section: Introductionmentioning
confidence: 89%
See 1 more Smart Citation
“…Similarly, through hydrothermal route, [40] successfully synthesized 3D flower-like ZnO architectures assembled with numerous nanosheets with the aid of SDS. It has also been demonstrated that SDS is a highly effective structuredirecting agent for producing box-like structures [41] and is observed elsewhere to cause complete suppression of the buckling phenomenon above an optimal value of 1% by weight [42]. Additionally, Blanch et al [39] found out that attractive depletion in SDS was preferential for carbon nanotubes of larger diameter at higher concentrations of SDS.…”
Section: Introductionmentioning
confidence: 89%
“…The anionic surfactant, sodium dodecyl sulfate (SDS) is perhaps one of the most widely studied surfactant with unique physical properties [33][34][35][36] that has found many applications in science and technology. The role of SDS in evaporation-driven assembly of nanoparticles have been widely explored [6,29,[37][38][39][40][41][42]. For example, [37] used SDS as a capping agent to synthesise rose-like BiOBr nanostructures with exposed {111} facets via a facile solvothermal route.…”
Section: Introductionmentioning
confidence: 99%
“…Hierarchical nano-structured materials have attracted significant research interest in recent years due to their owing features and possible applications in the fields of catalysis 1 , adsorption 2 and drug delivery 3 due to their high surface area and thermal stability. Out of different materials, aluminium oxides are broadly used in ceramics, refractories and abrasives due to their hardness, chemical inertness, high temperature resistance, electrical resistance and resistance to oxidation and corrosion [4][5][6] . Considering their various properties, synthesis and applications of nano-sized alumina or alumina composites is a challenging research topic in the field of material chemistry.…”
Section: Introductionmentioning
confidence: 99%
“…Herein, we report a facile hydrothermal process to synthesize the hierarchical mesoporous g-Al 2 O 3 with polysorbate-40 (Tween-40) as template and pore forming agent to improve their adsorption performance. Adsorption experiments were also compared with one of the previous work 6 . The hierarchical hollow structure can effectively promote the adsorption process under the action of capillary force caused by pores.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation